Mummies in the morning - Laird, Jenny; 1969-; Laird, Jenny; 1969-; Matthews, Kelly; (Comic book artist); Matthews, Nichole; Osborne, Mary Pope. (New York, 2022)
"The magic tree house has whisked Jack and Annie to ancient Egypt. Inside a pyramid, Jack and Annie find a long-dead queen who needs their help solving a centuries-old riddle. If only they can find their way through the pyramid's maze!"--
Keywords: (Fictitious character from Osborne); Fiction; (Fictitious character from Osborne); Jack; Fiction; (Fictitious character from Osborne); Jack; Comic books, strips, etc; Comic books, strips, etc; (Fictitious character from Osborne); Annie; Annie; Fiction; Fiction; Riddles; Fiction; Pyramids; Cartoons and comics; Comic books, strips, etc; Riddles; Comic books, strips, etc; Pyramids; Comic books, strips, etc; Mummies; Mummies; Egypt; Comic books, strips, etc; Egypt; Fiction; Graphic novels; Fantasy comics